2019
DOI: 10.1108/jqme-07-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

A sequential TPM-based scheme for improving production effectiveness presented with a case study

Abstract: Purpose The purpose of this paper is to improve production effectiveness of equipment by facilitating the implementation of the key principles of total productive maintenance (TPM). Design/methodology/approach A sequential TPM-based scheme consisting of 13 procedural steps is proposed. The steps cover the basic aspects of a generic improvement system, i.e. planning, implementation, checking, corrective action and control. Findings The proposed scheme was effective in increasing the overall equipment effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 26 publications
0
45
0
5
Order By: Relevance
“…The concept is later expanded to the maintenance and improvement of the production quality system, through the equipment, process and operator, and increases the commercial value of the product (Sharma & Singh, 2015;Parikh & Mahamuni, 2015). TPM implementation, which brings short and long-term improvements to the enterprise, including overall equipment efficiency (OEE) (Méndez & Rodríguez, 2017;Amorim, Hatakeyama & Rojas-Lema, 2018;Bataineh, Al-Hawari, Alshraideh & Dalalah, 2019). TPM minimizes the probability of equipment failure, manufacturing a non-conforming product and the occurrence of a safety accident (Patil & Raut, 2019).…”
Section: Total Productive Maintenance (Tpm)mentioning
confidence: 99%
“…The concept is later expanded to the maintenance and improvement of the production quality system, through the equipment, process and operator, and increases the commercial value of the product (Sharma & Singh, 2015;Parikh & Mahamuni, 2015). TPM implementation, which brings short and long-term improvements to the enterprise, including overall equipment efficiency (OEE) (Méndez & Rodríguez, 2017;Amorim, Hatakeyama & Rojas-Lema, 2018;Bataineh, Al-Hawari, Alshraideh & Dalalah, 2019). TPM minimizes the probability of equipment failure, manufacturing a non-conforming product and the occurrence of a safety accident (Patil & Raut, 2019).…”
Section: Total Productive Maintenance (Tpm)mentioning
confidence: 99%
“…Basically, TPM necessitates all individuals in the organisation from top management to floor staff be dedicated to the TPM programme (Bataineh et al, 2019). Generally, the philosophy of TPM embeds (Kanta Patra et al, 2005):…”
Section: Operation and Maintenance In Green Buildingmentioning
confidence: 99%
“…Typically, the application of TPM is more restrained in manufacturing industry (Weinstein et al, 2009, Bataineh et al, 2019. Nonetheless, its benefits are valuable to be practised in other industry, such as the construction industry (Andersson et al, 2015, Haddad, 2012, Jain et al, 2014, Kanta Patra et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsang et al (1999) suggested holistic approach to measure maintenance performance which should be linked to an organization's strategy in order to provide useful information for making effective decision and shaping desirable employee behaviour. Recently, Bataineh et al (2019) dealt with the same problem, by purposing a new TPM organization. In fact, in order to improve production effectiveness of equipment by facilitating the implementation of the key principles of TPM, the authors proposed 13 procedural steps, covering planning, implementation, checking, corrective action and control, in sequential TPM method.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%